2013
DOI: 10.1007/s11606-013-2701-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing 3 Values Clarification Methods for Colorectal Cancer Screening Decision-Making: A Randomized Trial in the US and Australia

Abstract: PURPOSE:To compare the effects of three methods of values clarification (VCM): balance sheet; rating and ranking; and a discrete choice experiment (DCE) on decision-making about colorectal cancer (CRC) screening among adults in the US and Australia. METHODS: Using online panels managed by a survey research organization in the US and Australia, we recruited adults ages 50-75 at average risk for CRC for an online survey. Those eligible were randomized to one of the three VCM tasks. CRC screening options were des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…All 3 showed differences regarding some measure of participants' most important attribute in the decision. 14,23,33 One of the comparisons showed difference in choice when the name of the intervention (prostate-specific antigen) was not given, but there was no difference when the name was given. 14 The other 2 studies showed no differences in choice.…”
Section: Comparisons Of Values Clarification Methods Against Each Othermentioning
confidence: 99%
“…All 3 showed differences regarding some measure of participants' most important attribute in the decision. 14,23,33 One of the comparisons showed difference in choice when the name of the intervention (prostate-specific antigen) was not given, but there was no difference when the name was given. 14 The other 2 studies showed no differences in choice.…”
Section: Comparisons Of Values Clarification Methods Against Each Othermentioning
confidence: 99%
“…[30] In general, values clarification methods increase citizens' attention to benefits and harms, and they are considered useful. [46] However, in this Danish setting, the paper format of the values clarification exercise was considered inapplicable. [23] In the present study, the The DA was distributed via email, because most citizens are expected to use eHealth solutions, since digital communication is mandatory.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Participants were given an opt-out option, “Given these options, I would not get screened”, for each choice task. Sawtooth Software Version 8 was used to design a balanced and efficient set of 16 DCE choice tasks for the English version of the survey; this number of questions has been shown in our past work to be feasible for English-speaking participants to complete [1, 19]. …”
Section: Methodsmentioning
confidence: 99%